Pengaruh Kesadaran Wajib Pajak dan Pelayanan Pajak terhadap Kepatuhan Wajib Pajak dalam Pembayaran PBB-P2 di Bandung - Habiburahman, Fadil; Darwati, Darwati; Yulianti, Yulianti; Sopandi, Encep (Indonesian Accounting Literacy Journal, 2025)
This study is driven by the significance of taxpayer compliance in the payment of Rural and Urban Land and Building Tax (PBB-P2), which is believed to be influenced by taxpayer awareness and the quality of tax services. The objective of this research is to examine the impact of taxpayer awareness and service quality on the level of compliance in fulfilling PBB-P2 obligations. A quantitative approach was employed, utilizing a descriptive associative research design. Primary data were obtained through questionnaires distributed to 100 taxpayers in the UPT Bapenda Bandung City. Sampling using purposive sampling technique with cluster sampling approach. The t-test and F-test were employed for hypothesis testing. Findings revealed that, both partially and jointly, taxpayer awareness and tax service quality significantly and positively affected compliance in paying PBB-P2.